![\boxed{(x - a)(x - b) = 0}](https://img.qammunity.org/2022/formulas/mathematics/high-school/5txw4ptt7fzoc78doyqdxktnt7gngasi2j.png)
The equation above is the intercept form. Both a-term and b-term are the roots of equation.
![x = - (1)/(3) \\ x = 5](https://img.qammunity.org/2022/formulas/mathematics/high-school/6wsx35kyink4ixcstzs9rqva5kgykk70gq.png)
These are the roots of equation. Therefore we substitute a = - 1/3 and b = 5 in the equation.
![(x + (1)/(3) )(x - 5) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/cno3p2p3qag5iqd68rpybyero0h8ppx9a0.png)
Here we can convert the expression x+1/3 to this.
![x + (1)/(3) = 0 \\ 3x + 1 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/5qdjjddi6ef9x0omadsj8zgrlklhzxlrro.png)
Rewrite the equation.
![(3x + 1)(x - 5) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/orj75k329j4i0t1hao8041cqj113uqrvy8.png)
Simplify by multiplying both expressions.
![3 {x}^(2) - 15x + x - 5 = 0 \\ 3 {x}^(2) - 14x - 5 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/vdjd5eqrpoh1ca1cnrzrkq1jpk4b9rstgz.png)
Answer Check
Substitute the given roots in the equation.
![3 {(5)}^(2) - 14(5) - 5 = 0 \\ 75 - 70 - 5 = 0 \\ 75 - 75 = 0 \\ 0 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/avlnirocebj6hugxiqgh06r4v9903rn9y7.png)
![3( - (1)/(3) )^(2) - 14( - (1)/(3)) - 5 = 0 \\ 3( (1)/(9) ) + (14)/(3) - 5 = 0 \\ (1)/(3) + (14)/(3) - (15)/(3) = 0 \\ (15)/(3) - (15)/(3) = 0 \\ 0 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/431c3plku1et6c3snzap4yasnpxnnm0err.png)
The equation is true for both roots.
Answer
![\large \boxed {3 {x}^(2) - 14x - 5 = 0}](https://img.qammunity.org/2022/formulas/mathematics/high-school/b15q73b6t8xs2v62vzq8yv9wra8ttrytc8.png)